A comprehensive approach to the diagnosis of the maxillomandibular skeletal pattern, body posture and craniocervical position - Yiliam Jiménez Yong; Mónica Machado Contreras; Olga Lidia Véliz Concepción; Eligio Eduardo Barreto Fiu; Luis Miguel Jiménez Mesa (Editorial Ciencias Médicas, 2022)
Introduction: Head and neck biomechanical principles are particularly relevant in the fields of orthodontics and dentomaxillofacial orthopedics. Any anomaly should be analyzed and treated within the cranio-cervical-mandibular system applying a comprehensive approach. Objective: Describe the relationship between the sagittal maxillomandibular skeletal pattern, body posture and craniocervical position in adolescents. Methods: A descriptive cross-sectional study was conducted from March 2018 to June 2019. The study sample was 105 adolescents attending seventh grade at Eduardo Anoceto Rega junior high school in Santa Clara. Determination was made of maxillomandibular skeletal patterns Classes I, II and III, measuring the facial convexity in Ricketts' cephalograms, craniocervical extension, normal inclination and flexion positions with Rocabado's cephalogram, and posture type with Bricot's method. Ethical standards were complied with. Use was made of the statistical tests chi-square, Fisher's F and Welch's. Results: Posture D (flat back and anterior scapular plane) prevailed in all skeletal classes: 64.76% of the adolescents, followed by posture C (posterior scapular plane). In Class II, posture D was followed by posture B (scapular and gluteal plane aligned with increased anterior curves): 6.22%. A predominance was observed of craniocervical normal inclination: 46.67% and flexion: 42.86%. In Class III, Rocabado's flexion and posteroinferior angle were more common than the remaining 107º skeletal classes. Conclusions: Cranial position with respect to cervical structures, according to the characteristics of each skeletal class, may be an important indicator in morphological diagnosis. Despite the large number of studies conducted in this field, consensus has not been achieved about the degree of relationship between craniocervical posture and malocclusions.